PENDIDIKAN MORAL DAN NILAI-NILAI AGAMA PADA ANAK USIA DINI: BUKAN SEKEDAR RUTINITAS - Farida Agus Setiawati (Paradigma, 2006)
negative behaviors of children, such as uttering impolite expressions, imitating violent actions, imitating adult activities not yet suitable to be acted out by children, and even committing suicide, have been practiced by many children nowadays. This phenomenon emerges because children often inappropriately imitate what they see, so that they behave improperly to the local norms or regulations. Lack of education and attention from their parents or other adults around them also plays and important role to the appearance of the children’s negative attitudes. The child period, especially the early ages from 0 to 8 years, is often called the golden years, during which various abilities and competencies grow and develop rapidly. Making the children accustomed to moral and religious values at this period will be very suitable; it will be deeply influential to the process of child development later. In some educational institutions designed for preschoolers, there are still many instructors trying to implement the moral and religious values by means of mere memorization in routine activities. As a result, the applied learning process is not quite well understood by the children, and thus not quite applicative. Consequently, the moral and religious values cannot be applied in the children’s daily activities. In that case, the objective of educating moral and religious values is not achieved. Educating moral and religious values to children will be better if taught by means of familiarizing the values in their daily activities. The learning process does not necessarily take place inside the classrooms, but it is better to be applied in various natural activities of the children. Cooperation with the parents or custodians to apply the moral and religious values in the children’s daily activities at home needs to be taken as well.Key words : moral, religious values, young children